ANALISIS IMPLEMENTASI STRATEGI PEMASARAN TERHADAP NASABAH BANK SYARI’AH NON MUSLIM - Asnawi Asnawi (JURNAL EKUIVALENSI, 2018)
The research examines the factors which effect non-muslem chinese to be the customer of Mega Shareah Bank of Indonesia. There are two basic questions composity the research. The first, what actually the dominant factor which determines their decisions to put trust on Mega Shareah Bank of Indonesia. For this purpose factor analysis technique is applied. The second, how it implies the marketing of Mega Shareah Bank of Indonesia, and thus, the result analysis of data process are detailed and described in The research result some answers from both of questions stated above. The dominant factor affecting non muslem chinese’s decision to put trust on shareah Mega Bank of Indonesia is promotion, which consist of six attributes, namelly, promotion broadcasted, via mass media (tv or newspaper), promotion engaged in mall in any public speak, promotion that is creatively and atractively packed, promotion delivered by public figure initial promotion of shareah Mega Bank applying no islamic jargon in marketing communication This dominant factor is actually not like the presumption of the research which is attributed by shareah factors